IDENTIFIKASI DAN MITIGASI PADA ZONA RAWAN GEMPA BUMI DI JAWA BARAT - -, Zufialdi Zakaria; -, Ismawan; -, Iyan Haryanto (Bulletin of Scientific Contribution, 2011)
Java Island is a region of frequent earthquakes with varying strength. Most of destructive earthquakes measuring over 5.6 on the Richter Scale, as a shallow earthquake with a depth of less than 30 KM. On land, the earthquake can damage a variety of infrastructure and endanger lives. At ocean, earthquakes tend to be a potential tsunami. The tsunami that ever happens is in the south of Pangandaran beach on July 27, 2006. To reduce the impact of the earthquake disaster, the identification and mitigation is required. In the identification of the earthquake in the mainland, the earthquake potential of fault-lines are shown on a large faults, there are: Earthquake's Row of Zone Bayah, Earthquake Row of Baribis Zone, Earthquake Row of Cimandiri Zone, Earthquake Row of Lembang Zone, Earthquake Row of Citanduy Zone. On the identification of the earthquake in the ocean, is required analysis to see the condition of the epicenter in the southern Teluk Pelabuhan Ratu. Mitigation of earthquake disaster can be done, among others through the various activities that need to be socialized, assisted by experts from various disciplines.